A comparative analysis of nanocoated expanded polystyrene for sustainable infrastructure applications - Moamen A. Shekib; Emad S. Bakhoum; Mohamed M. Omran; Ahmed M. Ahmed; Irene Samy Fahim; Sherif S. AbdelSalam (Scientific Reports)
Abstract Engineers increasingly face challenges due to the demand for sustainable infrastructure; thus, this research evaluates different road embankment techniques based on sustainability. It compares the environmental impacts and economic feasibility of three road embankment techniques: using traditional soil backfilling, using expanded polystyrene (EPS) geofoam blocks with geomembrane protection, and using EPS blocks coated with a newly developed nanocoating material. Life Cycle Assessment (LCA) and Life Cycle Costing (LCC) methods are employed to measure the potential environmental loads and economic viability of a real-world twin-bay tunnel project. LCA has been performed with SimaPro software and using ReCiPe endpoint method. The findings indicate that EPS coated with nanocoating material has the lowest environmental impact and cost, with LCA single score of 1.06 MPt and cost reductions of about 14.5% and 27.48% compared to EPS with geomembrane and soil backfilling, respectively. Traditional soil backfilling has the highest environmental impact with a single score of 2.52 MPt. In comparison, EPS with geomembrane has a single score of 2.477 MPt offering a 15.17% cost reduction compared to soil backfilling. Sensitivity analysis concludes that the required amount of reinforced concrete for the tunnel significantly impacts the results. The outcomes support sustainable decision-making for infrastructure solutions.